Ekoteologi dalam Tafsir Ayat-Ayat Ekologi Kementerian Agama Republik Indonesia - M Badruz Zaman; Achmad Azis Abidin; Ida Lailatin; Muhammad Nahjul Fikri; Ahmad Nashrullah (Lajnah Pentashihan Mushaf Al-Qur'an, 2026)
Amid the escalating global ecological crisis, religious discourse is increasingly expected to provide ethical and theological foundations for environmental responsibility. This article examines Tafsir Ayat-Ayat Ekologi as a pioneering effort to construct a coherent Islamic eco-theological paradigm. Employing a qualitative hermeneutical approach, this study analyzes how the tafsir systematically reinterprets key Qur’anic concepts—taskhir, tawhid, khalifah–amanah, and mizan–anti-fasad—into a theologically grounded framework for ecological ethics. The findings reveal that the tafsir successfully bridges classical exegetical traditions and contemporary ecological concerns, shifting from an anthropocentric worldview toward a theo-anthropocentric paradigm grounded in divine accountability and ecological restraint. This study contributes to the formulation of an “Islamic ecological hermeneutics” that is both authoritative and contextually rooted in the Indonesian Muslim experience. Moreover, the tafsir positions religious authority as a moral agent in addressing the planetary crisis by providing normative legitimacy for green transformation across multiple sectors. Nevertheless, its transformative impact ultimately depends on effective institutional translation into public policy, education, and religious norms, thereby offering a complex yet promising pathway for embedding ecological ethics within the Islamic public sphere in Indonesia and beyond.